2004
DOI: 10.1143/jjap.43.l540
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Y-Doped Polycrystalline SrTiO3

Abstract: The thermoelectric properties of Y-doped polycrystalline SrTiO3 (Sr1-x Y x TiO3) are measured from 10 K to 900 K. The Y component is doped up to the solubility limit of Sr1-x Y x TiO3, x=0.1. The Y-doped polycrystalline samples show a low resistivity, ∼1 ×10-5 Ω·m and a large absolute value of the Seebeck coefficient, ∼150 µV/K, at room temperature. Consequently, they have a high power factor, 1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 13 publications
8
52
2
Order By: Relevance
“…Obara et al reported the highest ZT of 10% Y-doped SrTiO 3 was 0.1 at 490 K. 4) However, in our case, the ZT value at corresponding temperature was in the order of 10 À2 . The difference in ZT value seems to come mainly from the difference in the electrical conductivity, namely, Obara's sample showed the electrical conductivity of about 10 5 Sm À1 , whereas, ours in the order of 10 3 Sm À1 .…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Obara et al reported the highest ZT of 10% Y-doped SrTiO 3 was 0.1 at 490 K. 4) However, in our case, the ZT value at corresponding temperature was in the order of 10 À2 . The difference in ZT value seems to come mainly from the difference in the electrical conductivity, namely, Obara's sample showed the electrical conductivity of about 10 5 Sm À1 , whereas, ours in the order of 10 3 Sm À1 .…”
Section: Resultscontrasting
confidence: 63%
“…However, no n-type oxide thermoelectric material with sufficient performance has been developed yet. We have focused our attention to strontium titanate as a promising n-type thermoelectric oxide material [4][5][6][7][8] in this study. This material has a high ability of thermoelectric performance, but has a high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…This value is comparable with the maximum obtained for Sr 1 x La x TiO 3 17 and noticeably higher than that for La 0.1 Sr 0.9 x Dy x TiO 3 , 22 Sr 1 x Ce x TiO 3 , 41 and Sr 1 x Y x TiO 3 materials. 42 The highest power factor of Sr 0.90 Pr 0.10 TiO 3 is provided by sharp increase in conductivity, whilst corresponding decrease in Seebeck coefficient is rather moderate. The results emphasize a high potential of substitution with praseodymium in approximate range of x ¼ 0.07 0.15 for improving the power factor of strontium titanate; for the latter, further optimization of praseodymium content is required.…”
Section: -4mentioning
confidence: 93%
“…For x 0.10, formation of point defects due to Pr addition is beneficial for improved phonon scattering and, thus, for lower lattice thermal conductivity, in agreement with the results obtained for various (Sr,Ln)TiO 3 materials. 17,21,42 In opposite to the negative effect on electronic conduction, distortion of perovskite lattice and weakening of Ti-O bonds may also provide stronger phonon-lattice interactions, resulting in lower j ph . 43 At the same time, the electronic thermal conductivity becomes significant at high carrier concentration: the j el contribution to the thermal conductivity increases from 1% 5% for x 0.05 up to 15% 20% in the case of Sr 0.90 Pr 0.10 TiO 3 ( Fig.…”
Section: -5mentioning
confidence: 99%
“…Material family References Mn oxide [49][50][51][52][53][54][55][56][57][58][59][60] ZnO, SrTiO 3 33, [61][62][63][64][65][66][67][68][69][70][71][72] Co oxide 34,35,[73][74][75][76][77] other oxide 28,63,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Si-Ge …”
Section: Acknowledgementmentioning
confidence: 99%